A case of hedonic perception of foreigners towards Chinese culture-specific odors from scent marketing perspective - Vinnikova, Anna (Archives of Business Research, 2016)
In a modern day competitive business environment, retailers can not rely only on conventional forms of marketing. It is important to find new original ways to influence the consumers. That is why many retailers turn to a new area of marketing called sensory marketing. The present study uses scent marketing techniques to investigate hedonic perception and verbal affective response of foreigners towards Chinese culture-specific odors. Our research has employed participants from over 40 countries to analyze the perception of Chinese odors. In this study, we attempt going beyond the stimulus-organism-response (SOR) model. Our findings reveal that culture, ethnic origin, duration of stay and association with Chinese culture are important variables in culture-specific odor perception. We further claim that consumer perception of smell is moderated by past experience and self-association with the culture. Our results suggest that odor affective response involves a complex emotional process. These emotions, are formed by the amount of interactions with a particular odor and context in which the odor is experienced.